Environmental-Related Trigger for Asthma in East Java: An Advance Analysis of the Risk Factor - Shahira Putri Primarani; Hario Megatsari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: According to the Indonesian Ministry of Data and Information Center (2019), the main cause of asthma is not yet known. The national prevalence of asthma is 4.0%. Meanwhile, according to Basic Health Research in 2019, the incidence of asthma in Indonesia was 2.4%, and in East Java, it was 2.5%. Several risk factors for the prevalence of asthma due to unhealthy behaviours, namely smoking consumption habits, physical activities, triggers for depression, and processed chicken/meat/fish foods that are given preservatives. Methods: The design of this study is the advanced analytical method. An approach of utilizing secondary data from the 2019 National Riskesdas (Basic Health Research) report. This study looked at the relationship between asthma prevalence and smoking habits, physical activity, triggers for depression, and consumption of processed chicken/meat/fish food with preservatives. Results: Based on the results, cigarette consumption habits and triggers of depression had a relationship with risk factors for asthma prevalence. Meanwhile, physical activity and consumption of processed meat/chicken/fish foods with preservatives did not have a relationship with the incidence of asthma. Conclusion: The increasing prevalence of asthma was closely related to smoking habits and a trigger for depressive disorders. However, based on the cross-tabulation results, there was no relationship between physical activity and consumption of processed meat/chicken/fish foods with preservatives and the prevalence of asthma. It is hoped that with this research, and seeing that there were still exposure factors from smoking habits and depression triggers, prevention efforts can be made, starting with education about asthma recurrence by avoiding smoking or air pollution, allergens, stress, and emotions. In addition, reducing asthma can be done by asking for support from the closest people to minimize these behaviors and changing smoking behavior with other positive habits such as getting used to replacing nicotine with candy.